A critical review of highway slope instability risk assessment systems - Pantelidis, Lysandros (My University, 2011)
This paper reviews existing highway slope instability risk assessment systems. It demonstrates that both quantitative and qualitative systems have some major disadvantages with a common characteristic being the lack of emphasis on the geology and geomorphology of slopes. Furthermore, the role of climatic conditions (the most common landslide triggering factor) is diminished or even ignored. It is noted that the existing risk assessment systems focus either on only one category of consequences (e.g. travellers’ safety) or simply sum the scores of more than one category, which may lead to an under-estimation of the significance of a consequence category. Finally, the suitability and reliability of the most commonly used consequences factors are discussed.
Keywords: Qualitative landslide risk assessment; Quantitative landslide risk assessment; Rockfall hazard rating system; Highway slopes